The Logical Path of PE Teachers' Ideological and Political Thinking Construction under the Background of IAPC - zhang, hui (Pacific International Journal, 2022)
The study of the logical path of the construction of physical education teachers' ideological and political thinking in the context of Ideological and Political Thinking Curriculum (IAPC) is to solve the problem of the lack of talents in the process of building physical education IAPC, which is conducive to the effective advancement of physical education IAPC. This study uses literature, logical reasoning, and analytical comparison methods to investigate the historical logic, realistic logic, and unrealistic logic of the construction of physical education teachers' ideological and political thinking in the context of IAPC. The study concluded that: 1.the historical logic of the construction of physical education teachers' ideological and political thinking is divided into three stages: saving the country through sports, raising the country through sports, and building the country through sports; 2.the realistic logic includes the incomplete physical education teachers' ideological and political thinking system; incomplete progress and integration, structural fault and integration , rigid method and stage integration, dimensional separation and muti-dimension integration. 3. Future logic includes open thinking, shared thinking, scientific thinking, and innovative thinking.